Bilateral incomplete cleft lip - Queiroz, Sormani Bento Fernandes; Filho, Jose Ferreira Cunha; De Lima, Valthierre Nunes [UNESP]; Bonardi, Joao Paulo [UNESP]; De Oliveira Puttini, Igor [UNESP]; Filho, Osvaldo Magro [UNESP] (Wolters Kluwer, 2016)
Patients with cleft palate and cleft lip have severe functional and aesthetic problems, if this deformity is not treated properly and in time, can also cause psychological and aesthetic problems to the patients. This study reports a case of a 22-year-old patient with incomplete bilateral cleft lip, addressing aspects related to the diagnosis, treatment planning, surgical technique, and postoperative follow-up of the patient. Surgical treatment of cleft lip and cleft palate consists of suturing the lip and the palate, and aims not only the aesthetic restoration, but also the recovery of the phonation, mastication and respiration, as well as a normal psychosocial development.
Keywords: Cleft lip; Cleft palate; Mouth abnormalities